A wide-speed high torque capability utilizing overmodulation strategy in DTC of induction machines with constant switching frequency controller - Jidin, Auzani; Nik Idris, Nik Rumzi; Mohamed Yatim, Abdul Halim; Sutikno, Tole; Elbuluk, Malik E. (IEEE, 2012)
This paper presents a simple overmodulation method employed in direct torque control (DTC) constant switching frequency (CSF) controller of induction machines. The proposed overmodulation method is utilized to extend a constant torque region and hence produce high torque capability in field-weakening region with six-step operation. It will be shown that the overmodulation operation using the DTC-CSF scheme can be established by controlling the stator flux locus from circular to the hexagonal shape. This is achieved by modifying the flux error status produced from the flux hysteresis controller before it is fed to the lookup table. The main benefit of the proposed method is its simplicity since it requires only a minor modification to the conventional DTC hysteresis-based structure and does not require a space-vector modulator.